Título de la tesis: Análisis del líquido seminal y su aporte al diagnóstico de infertilidad - Katherine Mishel, Erazo Paredes (2022)
ABSTRACT: Infertility is a relevant disease in our society, which affects couples and has increased in recent years. This research aimed to gather information on the seminal fluid analysis and its contribution to timely diagnosis. This review was based on a cross-sectional and retrospective descriptive study of non-experimental documentary design. The population consisted of 109 bibliographic references to which the inclusion and exclusion criteria were applied, where 77 publications taken from scientific databases were selected. The analysis and discussion of the results concluded that examining this fluid is essential to identify a male who presents infertility. These tests provided the most outstanding contribution to the diagnosis where the spermiogram is essentially applied to give an initial assessment to the patient, in which most of those affected presented alterations in sperm motility and morphology. The evaluation of sperm DNA fragmentation is performed through the TUNEL assay, comet, dispersion test, and sperm chromatin structure, which is associated with alterations in seminal parameters and was demonstrated with the review of several articles. The analysis is complemented by sperm culture and anti-spermatozoa antibody test performed by mixed antiglobulin and immunosphere reaction techniques. The leading causes of infertility are advanced age, smoking, and drug use. Key words: infertility, semen, spermatozoa, spermogram, sperm DNA.